2018
DOI: 10.1159/000486098
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Treatment during the Intravitreal Melphalan Era: Concurrent Intravitreal Melphalan and Systemic Chemoreduction

Abstract: Background: Intravitreal injection of melphalan (IVM) is safe and effective for the treatment of seeding in retinoblastoma. Current protocols require weekly injections during examination under anesthesia (EUA). To avoid additional anesthesia exposure for these children, IVM was initiated at the EUA concurrent with the 4th cycle of systemic chemoreduction in a series of 6 patients with persistent seeding. Methods: A retrospective review was completed to assess treatment response compared to all patients at our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…Incorporation of iVitc can potentially improve ocular survival rates to 71% (500 + 66/797) from 63% (without use of iVitc), which seems to be comparable to results reported with IAC [15]. In fact, a few recent studies have shown improved ocular survival (70-80%) with use of concurrent or subsequent administration of iVitc for refractory or recurrent vitreous seeding [13,[36][37][38][39][40]. Similar enhancing effect on ocular survival has also ■ Control ■ Recurrence: Other ■ Recurrence: Vitreous seeding Fig.…”
Section: Discussionsupporting
confidence: 66%
“…Incorporation of iVitc can potentially improve ocular survival rates to 71% (500 + 66/797) from 63% (without use of iVitc), which seems to be comparable to results reported with IAC [15]. In fact, a few recent studies have shown improved ocular survival (70-80%) with use of concurrent or subsequent administration of iVitc for refractory or recurrent vitreous seeding [13,[36][37][38][39][40]. Similar enhancing effect on ocular survival has also ■ Control ■ Recurrence: Other ■ Recurrence: Vitreous seeding Fig.…”
Section: Discussionsupporting
confidence: 66%
“…Several recent clinical treatment protocols for intravitreal injections with melphalan have decreased the frequency even further, to every 2 weeks or every 3 weeks, while maintaining good efficacy. 9 , 17 , 45 Less frequent belinostat dosing might likewise maintain the same excellent efficacy-to-toxicity ratio and therapeutic window seen here. Our protocol of three weekly injections did not eliminate 100% of tumor cells quantified in the vitreous.…”
Section: Discussionmentioning
confidence: 54%
“…Intravitreal chemotherapy with melphalan and/or topotecan is increasingly used in conjunction with IA therapy for better and durable control of vitreous seeds. The integration of intravitreal melphalan with systemic chemotherapy with carboplatin, etoposide, and vincristine has also been shown to be promising 25 …”
Section: Discussionmentioning
confidence: 99%